Current situation and perspectives of school libraries in Costa Rica - Van Patten de Ocampo, Elia María (1980)
In the past the school libraries of Costa Rica were representing sites without any attraction. In a lot of time they were out of context in the National Planning of Educational Development, principally for economic factors. At present the school libraries are in a process of change where they seek to have a fundamental paper in the attainment of the aims of the Costa Rican education.